Respuesta :

Answer:

y= ab    if a≠b

Step-by-step explanation:

y/a −b= y/b −a

multiply each side by ab to clear the fractions

ab(y/a −b) = ab( y/b −a)

distribute

ab * y/a - ab*b = ab * y/b - ab *a

b*y - ab^2 = ay -a^2 b

subtract ay on each side

by -ay -ab^2 = ay-ay -a^2b

by -ay -ab^2 =-a^2b

add ab^2 to each side

by-ay -ab^2 +ab^2 = ab^2 - a^2b

by-ay = ab^2 - a^2b

factor out the y on the left, factor out an ab on the right

y (b-a) = ab(b-a)

divide by (b-a)

y (b-a) /(b-a)= ab(b-a)/(b-a)    b-a ≠0   or b≠a

y = ab